SEMANTICS ERRORS COMMITED BY INDONESIAN CELEBRITIES: CLASSIFICATIONS AND MEANINGS - dwinesa anggraeni (Scope : Journal of English Language Teaching, 2020)
Abstract Examining and studying semantics error is a challenging area, due to the position of English as the foreign language in Indonesia. The skill of Indonesian in using English might be as not as good as Singaporean, Malaysian, or Filipinos. Indonesian try to use some English words in their daily conversation or certain occasion. However, they tend to ignore the meanings, as the result the words used are semantically incorrect. Insufficient knowledge of English semantic system causes Indonesian just accept the English words they got from media especially from their favourite Indonesian celebrities, without thinking the meanings might be wrong. In order to figure out the problem, this research aims to examine the semantics errors used by Indonesian celebrities on social media, TV show, and online news, how they can be categorized into errors classifications based on Shormani and Al-Sobani’s (2012) theory that basically followed the error taxonomy from James (1998). This research also investigated the meanings because knowing the meanings of the words is also very helpful in avoiding the errors of using English. The semantic errors that classified in this study are formal misselection, formal misformation, lexical choice, collocation, and lexicogrammatical choice.  The researcher uses qualitative descriptive method in doing the research. There are two kinds of data used in this research, written and oral data from Indonesian celebrities’ social media, TV show, online news, including videos on YouTube.Key word: Semantics errors, classification, meanings, Indonesian celebrities ABSTRAKMeneliti dan mempelajari kesalahan pada makna, adalah hal yang menantang. Kemampuan orang Indonesia dalam menggunakan bahasa Inggris mungkin tidak sebaik orang Singapura, Malaysia, atau Filipina. Orang Indonesia mencoba menggunakan beberapa kata bahasa Inggris dalam percakapan sehari-hari atau dalam kegiatan tertentu. Walaupun demikian, mereka cenderung mengabaikan maknanya, sebagai dampaknya kata-kata yang digunakan tersebut tidak tepat secara semantik. Pengetahuan sistem semantik bahasa Inggris yang kurang menyebabkan orang Indonesia hanya menerima kata-kata bahasa Inggris yang mereka dapat dari media, khususnya dari selebritas Indonesia fovorit mereka, tanpa berfikir mungkin maknanya salah. Untuk memecahkan masalah ini, penelitian ini bertujuan untuk meneliti kesalahan semantik yang digunakan selebritas Indonesia dalam media sosial, acara TV, dan berita online, bagaimana kesalahan tersebut dikelompokkan dalam klasifikasi- klasifikasi kesalahan menurut teori Shormani dan Al-Sobani’s (2012) yang pada dasarnya mengikuti sistem taksonomi kesalahan teori James (1998). Penelitian ini juga menginvestigasi maknanya karena mengetahui makna kata juga sangat membantu untuk menghindari kesalahan dalam penggunaan bahasa Inggris. Kesalahan semantik yang diklasifikasikan dalam penelitian ini adalah salah pemilihan dalam bentuk formal, salah pembentukan dalam bentuk formal, pemilihan kata, dan pemilihan gramatikal kata. Peneliti menggunakan metode deskriptif kualitatif dalam penelitian ini. Terdapat dua jenis data yang digunakan, data tertulis dan lisan dari media sosial selebritas, acara TV, berita online, termasuk video di YouTube. Kata kunci: Kesalahan semantik, klasifikasi, makna, selebritas Indonesia